2021
DOI: 10.1007/s10877-020-00645-1
|View full text |Cite
|
Sign up to set email alerts
|

The influence of depth of anesthesia and blood pressure on muscle recorded motor evoked potentials in spinal surgery. A prospective observational study protocol

Abstract: For high-risk spinal surgeries, intraoperative neurophysiological monitoring (IONM) is used to detect and prevent intraoperative neurological injury. The motor tracts are monitored by recording and analyzing muscle transcranial electrical stimulation motor evoked potentials (mTc-MEPs). A mTc-MEP amplitude decrease of 50–80% is the most common warning criterion for possible neurological injury. However, these warning criteria often result in false positive warnings. False positives may be caused by inadequate d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Since there is no method that can directly measure the perfusion of these tissues, the measurement and regulation of blood pressure is of great importance. In a recent study, the depth of anesthesia and mean arterial pressure values were stated to affect the optimal measurements of MEP [14]. In our study, the target MAP values were determined as 55-110 mmHg.…”
Section: Discussionmentioning
confidence: 87%
“…Since there is no method that can directly measure the perfusion of these tissues, the measurement and regulation of blood pressure is of great importance. In a recent study, the depth of anesthesia and mean arterial pressure values were stated to affect the optimal measurements of MEP [14]. In our study, the target MAP values were determined as 55-110 mmHg.…”
Section: Discussionmentioning
confidence: 87%
“…4 Distribution of optimal ISI when measuring mTc-MEPs using supramaximal stimulation with a pulse duration of 0.075ms (n = 29) The x-axis denotes the different muscles used for mTc-MEP monitoring and the y-axis denotes the number of patients. The optimal ISI's ranging from 1ms to 4ms are presented by the different colored bars for the AH left, AH right, TA left and TA right separately the effects of higher anesthetic drug doses, anesthetic fade, and significant blood pressure decreases on mTc-MEP amplitudes [20][21][22]. Although, the ≥ 20 V cut-off value chosen in this study is arbitrary, in our experience, it was sufficient to counteract for anesthetic events.…”
Section: Interstimulus Intervalmentioning
confidence: 99%
“…In three patients, supramaximal stimulation was not achieved although the subsequent analyses showed that there had still been the possibility to increase the voltage without reaching the maximal current output. These three anesthetic fade, or significant blood pressure decreases cause reductions in mTc-MEP amplitudes then it is desirable to increase the stimulation voltage or current [20,21]. Therefore, we evaluated if there was the possibility to increase the stimulation voltage with ≥ 20 V below maximum output to address for these possible anesthetic events.…”
Section: Patientsmentioning
confidence: 99%
“…It is currently not clear what blood pressure is sufficient to ensure spinal cord perfusion [23 ▪▪ ] but decreasing the pressure below this level (of autoregulation) leads to progressive mTc-MEP and SSEP amplitude decreases without affecting latency [21,24]. Adhering to the generally accepted population-based lower and upper MAP threshold of 60–70 mm Hg and 160 mm Hg [25] and adjusting these targets by monitoring the EPs is advisable.…”
Section: Intraoperative Managementmentioning
confidence: 99%